2021
DOI: 10.1002/hed.26893
|View full text |Cite
|
Sign up to set email alerts
|

Treatment modalities, adverse events, and survival outcomes in older patients with head and neck squamous cell carcinoma

Abstract: Background: Chemoradiation with curative intent in older adults with locally advanced head and neck squamous cell carcinoma (HNSCC) has been a challenge, because of its potential toxicities.Methods: We selected primary HNSCC cases from the SEER-Medicare linked database, assessed overall survival (OS) and adverse events and their associations with different treatments, across four age groups including the youngest (66-69 years) and the oldest (≥80 years).Results: Better OS was associated with chemoradiation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, this is consistent with our data from OPSCC, suggesting that overall performance status is more important than the physical age of the patient. Also, this is consistent with the suggestion that not only chronological but also biological age and functional status (and probably other factors) should be considered when selecting the best cancer treatment [ 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, this is consistent with our data from OPSCC, suggesting that overall performance status is more important than the physical age of the patient. Also, this is consistent with the suggestion that not only chronological but also biological age and functional status (and probably other factors) should be considered when selecting the best cancer treatment [ 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…The authors concluded that patient characteristics other than age should be considered equally in selecting the best therapy for elderly patients. 19…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multimodal treatment and surgical treatment were associated with improved OS, and radiation therapy alone was associated with worse functional outcomes in multivariate analysis for the entire cohort and the oldest cohort (≥80 years). The authors concluded that patient characteristics other than age should be considered equally in selecting the best therapy for elderly patients 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this broad age spectrum, variations in treatment outcomes may exist among different age subgroups. Several cohort studies have indicated that elderly patients can safely undergo definitive chemoradiotherapy and derive benefits from it [4]. However, for subgroups exceeding the age range of 78-80 in developed countries, the acceptability of such treatments may be diminished.…”
Section: Introductionmentioning
confidence: 99%